2022
DOI: 10.1021/acsomega.1c05907
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Staged and Direct Fast Pyrolysis Behavior of Waste Pine Sawdust Using High Heating Rate TG-FTIR and Py-GC/MS

Abstract: To understand the fast pyrolysis kinetics and product evolution of waste pine sawdust, high heating rate thermogravimetry-Fourier transform infrared (TG-FTIR) was used to obtain the kinetic parameters and the chemical groups formed during the pyrolysis process, while pyrolysis-gas chromatography/mass spectrometry (Py-GC/MS) was used to investigate the detailed compositions of products under the staged (seven stages from 300 to 600 °C) and direct fast pyrolysis process. Spectral bands were identified for acids,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 61 publications
1
3
0
Order By: Relevance
“…The GCMS analysis unveils that the liquid sample predominantly contains aliphatic hydrocarbons and aromatic compounds within the range appropriate for transport‐grade diesel. The carbon distribution in this liquid fuel encompasses C 8 to C 28 , closely mirroring findings documented in established literature 63,66 . The GC–MS spectra primarily exhibit alkanes (approximately 41 wt.%) and alkenes (around 20 wt.%), resulting from the thermal conversion of W40P60.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…The GCMS analysis unveils that the liquid sample predominantly contains aliphatic hydrocarbons and aromatic compounds within the range appropriate for transport‐grade diesel. The carbon distribution in this liquid fuel encompasses C 8 to C 28 , closely mirroring findings documented in established literature 63,66 . The GC–MS spectra primarily exhibit alkanes (approximately 41 wt.%) and alkenes (around 20 wt.%), resulting from the thermal conversion of W40P60.…”
Section: Resultssupporting
confidence: 76%
“…The carbon distribution in this liquid fuel encompasses C 8 to C 28 , closely mirroring findings documented in established literature. 63,66 The GC-MS spectra primar- Furthermore, during the propagation phase, a free radical bearing an unpaired electron on a carbon atom undergoes β-scission, forming alkenes. 69 The relatively low content of cyclic hydrocarbons (16.3%) suggests that the pyrolysis of WP does not favor processes like cyclization and amortization.…”
Section: Gc-ms Analysismentioning
confidence: 99%
“…Previously, some researchers have performed the pyrolysis of pine sawdust to investigate basic characteristics (Gao et al 2013, Tian et al 2021, Zhang et al 2022a). However, only a few studies can be found associated with pyrolysis process and potential application of biochar derived from fermentation pine sawdust.…”
Section: Introductionmentioning
confidence: 99%
“…While incineration releases toxic fumes into the environment, landfilling of e-waste can lead to leaching of potentially hazardous materials into the environment. , Recently, thermochemical techniques have grown remarkably as an efficient methodology for treating e-waste, particularly PCBs. Pyrolysis is one such technique that produces solid char, liquid tar, and gases as the final products from a particular polymer or organic feedstock. The advantage of pyrolysis of PCBs is that, if the temperature is high enough, it will melt the solder used for attaching the different components. Hence, the simultaneous recovery of the organic fraction and removal of the solder material will aid in the removal of the metallic fraction from the organic fraction. …”
Section: Introductionmentioning
confidence: 99%